2004
DOI: 10.1038/sj.onc.1207147
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JNK reduces G2/M transit independent of p53, leading to endoreduplication, decreased proliferation, and apoptosis in breast cancer cells

Abstract: c-Jun N-terminal kinase (JNK) is activated by diverse cell stimuli, including stress, growth factors, and cytokines. Traditionally, activation of JNK by stress treatment is thought to induce cell death. However, our recent data indicate that JNK's ability to sensitize cells to apoptosis may be, in part, cell cycle dependent. Here, we show that the majority of both paclitaxel-and UV-induced apoptosis can be inhibited by the pharmacological JNK inhibitor, SP600125, in MCF-7 cells. However, inhibition of JNK does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
126
5
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 40 publications
17
126
5
1
Order By: Relevance
“…These findings were also supported by the results of the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide (MTT) and terminal deoxynucleotidyl transferase biotin-dUPT nick end labeling (TUNEL) assays (data not shown). Although SP600125 has been shown to prolong mitotic progression (Du et al, 2004) and cause G2/M arrest (Mingo-Sion et al, 2004), we identified that 10 mM SP 600125 did not significantly interfere with paclitaxel-induced cell cycle profile change (Figure 2c and d). Nonetheless, 20 mM SP 600125 did change the cell cycle profiles (data not shown).…”
Section: Sp600125mentioning
confidence: 83%
See 1 more Smart Citation
“…These findings were also supported by the results of the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide (MTT) and terminal deoxynucleotidyl transferase biotin-dUPT nick end labeling (TUNEL) assays (data not shown). Although SP600125 has been shown to prolong mitotic progression (Du et al, 2004) and cause G2/M arrest (Mingo-Sion et al, 2004), we identified that 10 mM SP 600125 did not significantly interfere with paclitaxel-induced cell cycle profile change (Figure 2c and d). Nonetheless, 20 mM SP 600125 did change the cell cycle profiles (data not shown).…”
Section: Sp600125mentioning
confidence: 83%
“…In addition to its stabilizing effects on the microtubules and the subsequent cell cycle arrest in the G2-M phase, paclitaxel also induces the vast activation of signal-transduction pathways that may be associated with proapoptotic signaling (Blagosklonny and Fojo, 1999;Taxman et al, 2003). Among the proapoptotic signaling networks activated by paclitaxel (Meikrantz and Schlegel, 1996;Lee et al, 1997), the c-Jun Nterminal kinase (JNK) signaling pathway played an important role (Lee et al, 1998;Wang et al, 1999Wang et al, , 2000MacKeigan et al, 2000;Vivat-Hannah et al, 2001;Mingo-Sion et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…ERK phosphorylates more than 160 proteins, including transcription factors, enzymes, protein kinase relating to signal transduction, and so on, and it ultimately down regulates the expression of MITF and melanogenesis [27][28][29][30]. JNK, involved in proliferation and apoptosis cancer cells, also controls the melanogenesis by downregulating the expression of MITF [31][32][33].…”
Section: Transcriptional Regulation Of Melanogenesismentioning
confidence: 99%
“…Depending on the particular cell type, cell-cycle arrest is accompanied by increasing DNA accumulation or by cell death. 16,76,77 This mechanism may be responsible for the anti-cancer activity of several natural compounds with anti-JNK activity. 80,81 Interestingly, mouse embryonic fibroblasts derived from JNK1 -/-and JNK2 -/-mice revealed that these two kinases have somewhat different roles in cell cycle regulation: JNK2 -/-cells exhibit a shorter G 1 cell cycle phase, i.e., they enter S phase earlier than wild-type counterparts, while JNK1 -/-cells show the inverse phenotype, a longer G 1 phase than wild-type cells.…”
Section: Jnk1 and Jnk2 In Cell Cycle Regulationmentioning
confidence: 99%